2022
DOI: 10.3389/fvets.2022.989522
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations in equine appendicular muscle activity and movement occur during induced fore- and hindlimb lameness: An electromyographic and kinematic evaluation

Abstract: The relationship between lameness-related adaptations in equine appendicular motion and muscle activation is poorly understood and has not been studied objectively. The aim of this study was to compare muscle activity of selected fore- and hindlimb muscles, and movement of the joints they act on, between baseline and induced forelimb (iFL) and hindlimb (iHL) lameness. Three-dimensional kinematic data and surface electromyography (sEMG) data from the fore- (triceps brachii, latissimus dorsi) and hindlimbs (supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(29 citation statements)
references
References 72 publications
1
28
0
Order By: Relevance
“…It has been suggested that compensatory longitudinal rotations of the back and pelvis during iHL are driven by increased activity of NLS epaxial, as well as HL protractor muscles. 46 The significant increases in NLS longissimus amplitude observed in this study, as well as NLS superficial gluteal, biceps femoris and semitendinosus observed in St. George et al 16 support the realisation of increased lateral bending of the back towards the NLS and of the pelvis towards the LS. Taken together, these findings are the first to support postulated muscular adaptations for known compensatory weightbearing and movement patterns of the limbs, back, and pelvis during hindlimb lameness.…”
Section: Kinematic Adaptations Of Thoracolumbar and Pelvic Motion Dur...supporting
confidence: 83%
See 4 more Smart Citations
“…It has been suggested that compensatory longitudinal rotations of the back and pelvis during iHL are driven by increased activity of NLS epaxial, as well as HL protractor muscles. 46 The significant increases in NLS longissimus amplitude observed in this study, as well as NLS superficial gluteal, biceps femoris and semitendinosus observed in St. George et al 16 support the realisation of increased lateral bending of the back towards the NLS and of the pelvis towards the LS. Taken together, these findings are the first to support postulated muscular adaptations for known compensatory weightbearing and movement patterns of the limbs, back, and pelvis during hindlimb lameness.…”
Section: Kinematic Adaptations Of Thoracolumbar and Pelvic Motion Dur...supporting
confidence: 83%
“…Based on its anatomical location and attachments, it is thought to extend the spine when activated bilaterally in a concentric contraction, whereas unilateral concentric activation results in lateral bending and/or axial rotation. 16 Here, longissimus had a bilateral, biphasic activation pattern in each stride cycle, with each burst corresponding to the second half of HL stance, where thoracolumbar flexion occurs (Figures 1 and 5). This biphasic pattern is well-documented in sEMG studies of quadrupedal trot on a treadmill, 16,[35][36][37][38] with longissimus function generally attributed to eccentric activity that stabilises the thoracolumbar spine during passive flexion.…”
Section: Kinematic Adaptations Of Thoracolumbar and Pelvic Motion Dur...mentioning
confidence: 89%
See 3 more Smart Citations